1999
DOI: 10.1021/es990056x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Structure and Binding Affinity of Humic Substances for Polycyclic Aromatic Hydrocarbons:  Relevance of Molecular Descriptors

Abstract: Partition coefficients for the binding affinities of pyrene, fluoranthene, and anthracene to 26 different humic materials were determined by fluorescence quenching. Sources included isolated humic acids, fulvic acids, and combined humic and fulvic fractions from soil, peat, and freshwater as well as Aldrich humic acid. Each of the humic materials was characterized by elemental composition, ultraviolet absorbance at 280 nm, molecular weight, and for 19 samples, composition of main structural fragments determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
181
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(204 citation statements)
references
References 25 publications
21
181
1
1
Order By: Relevance
“…2B), while HS aromatic carbon content (percentage of peak area of 13 C NMR spectrum 110-165 ppm) has no linear relationship with log K OC values, with P > 0.1 for all the three PAHs. Although Perminova et al found that molecular weight was a poorer predictor than aromaticity and other 13 C descriptors [31], the prevalence of molecular weight over aromaticity in our study can be explained by several factors. First, discrepancy exists because almost all of their HS samples are from a terrestrial source and most are a combination of FA and HA.…”
Section: Relationship Between Hs Properties and Binding Affinity For contrasting
confidence: 91%
See 1 more Smart Citation
“…2B), while HS aromatic carbon content (percentage of peak area of 13 C NMR spectrum 110-165 ppm) has no linear relationship with log K OC values, with P > 0.1 for all the three PAHs. Although Perminova et al found that molecular weight was a poorer predictor than aromaticity and other 13 C descriptors [31], the prevalence of molecular weight over aromaticity in our study can be explained by several factors. First, discrepancy exists because almost all of their HS samples are from a terrestrial source and most are a combination of FA and HA.…”
Section: Relationship Between Hs Properties and Binding Affinity For contrasting
confidence: 91%
“…As pointed out by Wang et al ''pseudo-hysteresis" could be a manifestation resulting from nonattainment of equilibrium due to rate-limited diffusion before desorption was started [36]. Although most previous studies reported that the sorption of PAHs to various types of dissolved HS was completed within minutes and the extent of reversibility was unrelated to the sorption time [5,31,37], Haitzer et al have shown decreasing bioavailability with increasing contact times up to 12 days for one HS sample out of three tested [38]. However, our further study showed that for HS, a contact time of 6 days has no influence on partition coefficients (P < 0.05) (data unpublished); therefore pseudo-resistance associated with nonequilibrium of partition can be eliminated.…”
Section: Desorption Of the Bound Fractionmentioning
confidence: 97%
“…It was found that sorption capacity of HOCs was positively related to aromaticity of humic and fulvic acids (Perminova et al, 1999), and was negatively correlated with certain polarity indices of NOM derived from elemental ratios (Grathwohl, 1990;Xing et al, 1994). However, other investigators (Chefetz et al, 2000;Salloum et al, 2002) revealed that aliphatic carbon of NOM could significantly contribute to sorption of HOCs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, aquatic humic substances appear to have a higher electron accepting capacity than those derived from terrestrial environments (Royer et al, 2002;Scott et al, 1998). On a general basis, the shuttling capacity of humic matter is determined mainly by with its aromaticity (Aeschbacher et al, 2010;Chen et al, 2003), where carbohydrate fractions were found to be less redox-active than polyphenolic fractions (Chen et al, 2003) Soil organic matter aromaticity is also one of the main functional groups in determining sorption of petroleum hydrocarbons (Ehlers et al, 2010;Perminova et al, 1999). Surfaceadsorbed and freely dissolved humic matter were found to exhibit similar shuttling activities (Wolf et al, 2009).…”
Section: Quality and Origin Of Humic Mattermentioning
confidence: 99%